Sphingosine-1-phosphate recruits macrophages and microglia and induces a pro-tumorigenic phenotype that favors glioma progression - Arseni, Lavinia; Sharma, Rakesh; Mack, Norman; Nagalla, Deepthi; Ohl, Sibylle; Hielscher, Thomas; Singhal, Mahak; Engel, Robert; Augustin, Hellmut; Sandhoff, Roger; Herold-Mende, Christel; Tews, Björn; et al. (Cancers, 2023)
Glioblastoma is the most aggressive brain tumor in adults. Treatment failure is predominantly caused by its high invasiveness and its ability to induce a supportive microenvironment. As part of this, a major role for tumor-associated macrophages/microglia (TAMs) in glioblastoma development was recognized. Phospholipids are important players in various fundamental biological processes, including tumor-stroma crosstalk, and the bioactive lipid sphingosine-1-phosphate (S1P) has been linked to glioblastoma cell proliferation, invasion, and survival. Despite the urgent need for better therapeutic approaches, novel strategies targeting sphingolipids in glioblastoma are still poorly explored. Here, we showed that higher amounts of S1P secreted by glioma cells are responsible for an active recruitment of TAMs, mediated by S1P receptor (S1PR) signaling through the modulation of Rac1/RhoA. This resulted in increased infiltration of TAMs in the tumor, which, in turn, triggered their pro-tumorigenic phenotype through the inhibition of NFkB-mediated inflammation. Gene set enrichment analyses showed that such an anti-inflammatory microenvironment correlated with shorter survival of glioblastoma patients. Inhibition of S1P restored a pro-inflammatory phenotype in TAMs and resulted in increased survival of tumor-bearing mice. Taken together, our results establish a crucial role for S1P in fine-tuning the crosstalk between glioma and infiltrating TAMs, thus pointing to the S1P-S1PR axis as an attractive target for glioma treatment.